Resilience Revisited: What Ministers Need to Know About Borderline Personality Disorder - Schweitzer, Carol L. Schnabl (Pastoral psychology, 2015)
This article presents a summary of current research on borderline personality disorder and examines interventions that work as well as the consequences for ministers and congregations when they attempt to help individuals struggling with borderline personality disorder. I use primarily the works of Blaise Aguirre, Gillian Galen, Randi Kreger, Christine Lawson, Joel Paris, Kimberlee Roth, and Freda Friedman-as well as the published life stories of Caroline Kraus and Kiera Van Gelder as illustrative case studies of women who have documented their struggles with the disorder. I argue that resilience and resourcefulness in the lives of these individuals often present as anger, manipulation, and retaliation directed at ministers. This is especially the case when ministers and parish members attempt to set healthy boundaries with these individuals whose fears of abandonment are triggered when a healthy boundary feels like a failure of empathy. I also argue that the misguided resourcefulness of people with borderline personality disorder is a strength that may help them make the journey toward healthy relationships. I demonstrate that it is possible to help these individuals and members of their families move from reactions of rejection and retaliation to responses of resilience and resourcefulness if interventions occur early in the development of the disorder.